Theory Does Not Exist: Comparative Ancient and Modern Explorations in Psychoanalysis, Deconstruction, and Rhetoric - Miller, Paul Allen (Anthem Press, 2024)
A wide-ranging collection of essays that makes the case for the humanities as central to our self-understanding, for theory as the latest incarnation of a perennial concern with the relation between words and things, and for the ancient as constitutive of the modern.